The Aetiology and Management of Gastric Carcinoma in Japan - Tomiyama, Satoko (Trinity Student Medical Journal, 2006)
With the rapid development of modern technologies, Japan has increased its population's average lifespan to become the longest in the world. Since 1981, its industrial lifestyle has seen cancer as the leading cause of death in Japan, accounting for 31.1% of the total number of deaths in 2004. Gastric cancer ranked first in morbidity until replaced by lung cancer in 1992. However, it still remains an important malignancy with significant geographical, ethnic, cultural, and socioeconomic differences in distribution. Although genetic factors can predispose individuals to contracting the disease, the environment, particularly diet, contributes to between one-third and one-half of all gastric cancers. There are three distinct approaches to gastric cancer treatment in Japan: endoscopic, surgical and oncological. This article describes the techniques employed in the treatment of gastric cancer in Japanese hospitals in the context of its aetiology.